PERSEPSI STAKEHOLDER TERHADAP PENGGUNAAN ROLLER BARRIER DALAM SISTEM KESELAMATAN JALAN DI INDONESIA - Siti Rahma; Rudy Hermawan Karsaman; Aine Kusumawati; Mahesa Akbar (Racic : Rab Construction Research, 2026)
Roller barrier is a road safety barrier innovation that uses a rotating cylinder system to absorb collision energy. Although it has been installed at 15 road sections in Indonesia and proven to contribute to reduced accident fatalities, its adoption remains limited. This study aims to analyze the perceptions of key stakeholders toward roller barrier usage in Indonesia through a descriptive qualitative approach with a multi-informant study design. Data were collected through in-depth semi-structured interviews with the West Java Provincial Transportation Agency (Dishub) and roller barrier distributors in Indonesia. Analysis was conducted using thematic analysis (Braun & Clarke, 2006) with source triangulation. Results show that both stakeholder groups acknowledge the relative advantage of roller barriers over conventional guardrails, but significant barriers exist: high installation costs (IDR 17,000,000/meter), non-compliance with the minimum 40% Local Content Level (TKDN) requirement, limited vehicle crash test facilities in Indonesia, and regional budget constraints. Triangulation findings identified a perception gap between Dishub as policy users and distributors as market actors, particularly regarding regulatory readiness and procurement ecosystems. This study recommends accelerating national standardization, developing domestic production, and establishing adaptive financing schemes to promote wider adoption of roller barriers.